Cytological and Immunocytochemical Study of Bronchial Wash in Bronchogenic Carcinoma - Ali, Hussam H.; Hussein, Alaa G.; Abbass, Shaimaa F. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: - Carcinoma of the lung has became the most common type of cancer since 1985 & the most common cause of cancer death in both males & females. Aim of study: - To assess the diagnostic accuracy of bronchial wash cytology & application of immunocytochemical methods, using two tumor markers (low molecular weight cytokeratin & epithelial membrane antigen) for more accurate & precise diagnosis of lung tumors. Patients, materials and methods: - Fifty fifes suspected lung cancer cases according to their clinicoradiological examinations were included in this study. Bronchial wash cytology was performed for all the 55 patients. Smears were stained by conventional cytological stain in addition to immunocytochemial staining using low molecular weight cytokeratin & epithelial membrane antigen. The final results of bronchial wash were compared to histopathological results & final clinical diagnosis as. Results: - Cytological smears of bronchial wash revealed the presence of malignant cells in 33 cases (60%). The sensitivity of bronchial wash cytology was 82.5%; the specificity was 100.0%, with overall accuracy of 87.3%. Using cytokeratin staining, 26 cases (47%) were positive for malignant cells, & 29 were negative. The sensitivity, specificity & overall accuracy were 65%, 100%, & 74.5% respectively. With EMA staining, 19 cases (27%) were positive for malignant cells & 36 were negative. The sensitivity, specificity & overall accuracy were 47.5%, 100%, & 61.8% respectively. Combined use of CK & EMA raised the sensitivity to 72.5%, specificity of 100% & overall accuracy of 80%. Combined use of monoclonal antibodies & conventional cytology raised the sensitivity to 95%, specificity 100%, with overall accuracy of 96.3%. Conclusions: - Using more than one monoclonal antibody, or using combined conventional cytology & immunocytochemistry increase the sensitivity for detection of malignant cells in bronchial wash smears.